Thermal energy harvesting from the human body using flexible thermoelectric generator (FTEG) fabricated by a dispenser printing technique. (15th November 2016) - Siddique, Abu Raihan Mohammad; Rabari, Ronil; Mahmud, Shohel; Heyst, Bill Van
Abstract: In this paper, a manual dispenser printing-based fabrication technique has been developed to synthesize a flexible thermoelectric generator (FTEG). Fabricated FTEGs, printed on polyester fiber clothe, convert the thermal energy from the human body into electrical energy using the Seebeck effect. Two flexible prototypes (prototype A and prototype B) were fabricated using a manual dispenser printing technique with n -type (0.98Bi, 0.02Sb)2 (0.9Te, 0.1Se)3 and p -type (0.25Bi, 0.75Sb)2 (0.95Te, 0.05Se)3 thermoelectric (TE) materials. The fabricated prototypes consisted of 12 pairs of n -type and p -type legs connected by silver conductive threads. The experimental investigations were conducted to determine the characteristics and the electrical outputs of the fabricated prototypes. The open circuit voltage and power output of prototype A and prototype B were 22.1 mV and 2.21 nW, and 23.9 mV and 3.107 nW, respectively, at 22.5 °C temperature difference. The fabricated prototypes were also tested on the human body at different body conditions and were found to be very flexible, twistable, and durable with the substrate as well as conforming well to the human body. Highlights: Flexible thermoelectric generators were developed by a dispenser printing method. Theoretical analysis & experimental tests were performed on two prototypes. The prototypes were very flexible, twistable, and durable with the substrate. The voltage output is relatively higher than FTEGs reported in the literature.